First phase 1 clinical study of olaparib in pediatric patients with refractory solid tumors. Issue 15 (20th May 2022) - Takagi, Masatoshi; Ogawa, Chitose; Iehara, Tomoko; Aoki‐Nogami, Yuki; Ishibashi, Eri; Imai, Minoru; Kimura, Toshimi; Nagata, Masashi; Yasuhara, Masato; Masutani, Mitsuko; Yoshimura, Kenichi; Tomizawa, Daisuke; et al.
Abstract : Background: The survival of patients with high‐risk, refractory, relapsed, or metastatic solid tumors remains dismal. A poly(ADP‐ribose) polymerase (PARP) inhibitor could be effective for the treatment of pediatric solid tumors with defective homologous recombination. Methods: This open‐label, multicenter phase 1 clinical trial evaluated the safety, tolerability, and efficacy of olaparib, a PARP inhibitor, in pediatric patients with refractory solid tumors to recommend a dose for Phase 2 trials. Olaparib (62.5, 125, and 187.5 mg/m 2 twice daily) was administered orally every day (1 cycle = 28 days) using a standard 3 + 3 dose‐escalation design. Patients aged 3–18 years with recurrent pediatric solid tumors were eligible. Pharmacokinetic and pharmacodynamic analyses were performed. Results: Fifteen patients were enrolled and received olaparib monotherapy, which was well tolerated. The recommended phase 2 dose for daily administration was 187.5 mg/m 2 twice daily. Pharmacokinetics were dose proportional. The area under the concentration‐time curve from 0 to 12 h and the peak plasma concentration for 187.5 mg/m 2 twice daily in children were comparable to previous data obtained in a 200‐mg, twice‐daily cohort and lower than those in the 300‐mg twice‐daily cohort in adults. Pharmacodynamic studies demonstrated substantial inhibition of PARP activity. Two partial responses were observed in patients with Wilms tumor and neuroblastoma. Conclusions: This report is the first clinical trial to describe the use of a PARP inhibitor as monotherapy in children. Olaparib was well tolerated, with preliminary antitumor responses observed in DNA damage response‐defective pediatric tumors. Lay summary: This Phase 1 trial evaluated the efficacy and safety of olaparib in patients with refractory childhood solid tumors. Olaparib was well tolerated, achieving objective response in 2/15 patients. The DNA damage response was attenuated in nearly one‐half of advanced neuroblastoma patients, demonstrating the utility of the PARP inhibitor. The results support further investigation of olaparib as a new treatment for DNA damage‐response or repair‐defective pediatric cancers. Abstract : This report is the first clinical trial to describe the use of a poly(ADP‐ribose) polymerase inhibitor as monotherapy in children. Olaparib was well tolerated, with preliminary antitumor responses observed in DNA damage response–defective pediatric tumors.